Social constructions of femininity and masculinity and suicide attempts in Cuba - Alejandro Arnaldo Barroso Martínez (Social Medicine Publication Group, 2023)
There is a continuity between sex and gender. Not only does one have sex, but institutionalized social discourses and practices construct one's own identity. In this way, social constructions of gender mediate how we think, feel, and act. In this context, the present study aims to understand the relationship between experiences of masculinity and femininity and suicide attempts in Cuba to prevent suicide from a gender perspective. The phenomenological method was used through the in-depth semi-structured interview with four people, two males and two females. The results show that traditional constructions of gender have a bidirectional relationship with suicide attempts. These are normalized through social institutions such as the family and the community and exert a psychological pressure that affects both women and men through the differential significance of bodies and moral qualities. These pressures generate feelings of shame and loneliness and lead the person to attempt suicide when they frustrate the satisfaction of needs for meaning. Protective processes against suicide attempts were also found in the Cuban context.